2019
DOI: 10.1016/j.redox.2019.101287
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic contribution of melatonin to the treatment of septic cardiomyopathy: A novel mechanism linking Ripk3-modified mitochondrial performance and endoplasmic reticulum function

Abstract: The basic pathophysiological mechanisms underlying septic cardiomyopathy have not yet been completely clarified. Disease-specific treatments are lacking, and care is still based on supportive modalities. The aim of our study was to assess the protective effects of melatonin on septic cardiomyopathy, with a focus on the interactions between receptor-interacting protein kinase 3 (Ripk3), the mitochondria, endoplasmic reticulum (ER) and cytoskeletal degradation in cardiomyocytes. Ripk3 expression was increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 82 publications
3
52
0
Order By: Relevance
“…Myocardial inflammation is the hallmark of several cardiovascular disorders, such as myocardial infarction, myocardial ischemia-reperfusion injury, diabetic cardiomyopathy, and sepsis-related myocardial damage (Gebhard et al, 2018;Zhong et al, 2019). The immune cells and pro-inflammatory cytokines involved in the inflammatory process promote cardiomyocyte dysfunction, which contributes to cardiovascular disease progression, severity, and outcomes (Ziegler, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial inflammation is the hallmark of several cardiovascular disorders, such as myocardial infarction, myocardial ischemia-reperfusion injury, diabetic cardiomyopathy, and sepsis-related myocardial damage (Gebhard et al, 2018;Zhong et al, 2019). The immune cells and pro-inflammatory cytokines involved in the inflammatory process promote cardiomyocyte dysfunction, which contributes to cardiovascular disease progression, severity, and outcomes (Ziegler, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As additional justification for the use of melatonin to treat Ebola infections, it is well known that similar vascular damage induced by bacterial lipopolysaccharide also is ameliorated by melatonin. This has been repeatedly documented in experimental sepsis (68,69) and has also been observed in human newborns suffering with septic shock (70).…”
Section: Fig 1 Effects Of Melatonin On Ebola Virus Induced Hemorrhamentioning
confidence: 53%
“…Again, front and center are the ability of melatonin to inhibit pro-inflammatory cytokines, reduce oxidative stress, and support the immune system which synergistically would afford protection against the complications induced by the Ebola virus. Additionally, Andersen and co-workers (53) reminded the reader that under similar pathological circumstances of bacterial lipopolysaccharide toxicity melatonin maintains more normal endothelial function and reduces fatality as mentioned above (68)(69)(70).…”
Section: Fig 1 Effects Of Melatonin On Ebola Virus Induced Hemorrhamentioning
confidence: 99%
“…Receptor-interacting protein kinase3 (Ripk3) may regulate signaling pathways that are related to mitochondrial injury, endoplasmic reticulum stress, and cell scaffold balance. Zhong et al (2019) found that Ripk3 expression was increased in LPS-infected cardiomyocytes. Mitochondrial autophagy plays an integral role in cardiac dysfunction.…”
Section: Mitochondrial Dysfunction In Cardiac Myocytesmentioning
confidence: 97%
“…Melatonin can restore the physiological functions of mitochondria and endoplasmic reticulum, maintain the stability of cytoskeleton, and thus improve cardiac function in septic mice (Zhang et al, 2019). The study on molecular mechanism has shown that melatonin attenuates the expression of BAP31 that interacts with mitochondria-localized proteins and regulates mitochondrial function (Zhang et al, 2019;Zhong et al, 2019). Kokkinaki et al (2019) showed that chemically synthesized diglucoside (LGM2605) can reduce the accumulation of cardiac ROS, protect mitochondrial function in heart, reverse myocardial injury, and improve the survival rate in a mouse model of sepsis.…”
Section: Mitochondrial Targeted Therapymentioning
confidence: 99%